2009
DOI: 10.1016/j.physbeh.2009.01.021
|View full text |Cite
|
Sign up to set email alerts
|

Progesterone and medroxyprogesterone acetate differentially regulate α4 subunit expression of GABAA receptors in the CA1 hippocampus of female rats

Abstract: The Women’s Health Initiative trials – in which more extreme adverse outcomes were observed in the medroxyprogesterone acetate (MPA) + conjugated equine estrogen (CEE) arm, as compared to the CEE only arm – suggest that the addition of MPA to estrogen treatment has undesirable consequences. An important question raised by these results is whether the adverse outcomes observed in the progestin arm can be attributed to effects that are unique to MPA or are common to all progestins. In this study we explored the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 45 publications
(51 reference statements)
0
23
0
Order By: Relevance
“…Because estrogens and progestins have been shown to regulate the structure and function of the hippocampus [1,23,24,25,33,34,35], in our studies the postnatal temporal profile of hippocampal SRC-1 provided a possibility that the age-related decrease of hippocampal SRC-1 may be caused by changes in circulating female hormones with aging. To test whether the aging-related changes of SRC-1 expression were related to dysfunction of the aging ovary, we used ovariectomy to mimic circulating estrogen deficiency.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Because estrogens and progestins have been shown to regulate the structure and function of the hippocampus [1,23,24,25,33,34,35], in our studies the postnatal temporal profile of hippocampal SRC-1 provided a possibility that the age-related decrease of hippocampal SRC-1 may be caused by changes in circulating female hormones with aging. To test whether the aging-related changes of SRC-1 expression were related to dysfunction of the aging ovary, we used ovariectomy to mimic circulating estrogen deficiency.…”
Section: Discussionmentioning
confidence: 82%
“…The hippocampus is one of the most important targets of ovarian hormones; hippocampal synaptic plasticity can be regulated by estrogen [3,4,8] and progestins [23,24,25]. In the hippocampus, the mRNAs and proteins of steroid receptors such as estrogen receptor α and β (ERα and ERβ) and progestin receptor [23] are present, and these nuclear receptors function to regulate hippocampal neuronal excitability, synaptogenesis and plasticity redundancy as well as hippocampus-associated learning and memory [6,8,26].…”
Section: Introductionmentioning
confidence: 99%
“…It is unknown if progesterone and MPA have similar neural effects because few studies have directly compared them. Braden et al (2010) found that chronic MPA significantly and progesterone marginally decreased levels of glutamic acid decarboxylase in the hippocampus when administered via osmotic pumps However, a single injection of progesterone transiently down regulated mRNA expression of GABA a subunits, where as MPA did not (Pazol, Northcutt, Patisaul, Wallen, & Wilson, 2009). If MPA and progesterone result in different neural outcomes, they may differentially affect cognition.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic long-term treatment with E 2 down-regulates estrogen receptors (Brown, Scherz, Hochberg, & MacLusky, 1996), and levels of choline acetyltransferase increase after acute E 2 treatment but return to normal after chronic treatment in the basal forebrain (Gibbs, 1997). Furthermore, acute treatment with estrogen and progesterone resulted in decreases in GABA receptor subunit expression 12 hours, but not 24 hours after treatment (Pazol et al, 2009). Therefore long term chronic hormone treatment during aging might lead to a down regulation of estrogen receptors in cognitive brain regions and different behavioral outcomes than short term treatments.…”
Section: Discussionmentioning
confidence: 99%
“…For example, our laboratory and others have shown that progesterone decreased GAD65 + 67 protein levels in the hippocampus and increased GAD65 + 67 protein levels in the entorhinal cortex (Braden et al, 2010) as well as decreased GAD activity in several brain regions, including the dorsal hippocampus, as measured by kinetic studies (Wallis and Luttge, 1980). Furthermore, an in situ hybridization study revealed that 12 h after treatment, progesterone, but not MPA, reduced hippocampal mRNA expression of the α4 subunit of the GABA(A) receptor (Pazol et al, 2009), suggesting that different progestogens can have variable impacts on the GABAergic system. We recently showed that in a middle-age Ovx rat model, progesterone administration resulted in transient working memory impairments on a spatial memory task, but concomitant delivery of bicuculline, a GABA(A) receptor antagonist, obviated these memory impairments (Braden et al, 2015).…”
Section: Aging Ovarian Hormones and Altered Neural Systemsmentioning
confidence: 99%